Synergistic effect of a VCO-ethanol solvent mixture and ultrasound-assisted extraction in enhancing xanthone extraction from mangosteen pericarp - Yao, Zhengyuan; Wang, Xinsheng; Mohammad Rashedi, Ismail Fitry; Chong, Gunhean (Institution of Chemical Engineers, 2025)
Xanthone, a bioactive compound from mangosteen pericarp (MP), is increasingly valued for its applications in functional foods, cosmetics, and pharmaceuticals due to its diverse medicinal properties. However, optimizing extraction methods, particularly solvent selection and technique, remains a challenge. This study introduces an innovative binary solvent mixture of virgin coconut oil (VCO) and ethanol, combined with ultrasound-assisted extraction (UAE), to significantly enhance xanthone yield. Solubility studies of xanthone in ethanol-VCO mixtures were conducted at four temperatures (303.15–323.15 K) across eleven volume ratios (0:1–1:0). The results demonstrated that the mixed-solvent achieved superior xanthone solubility compared to pure ethanol or VCO, with the maximum solubility (0.0329 g/g) observed at a VCO mass fraction of 0.63 at 323.15 K. The Jouyban- Acree model was modified and successfully correlated the solubility data, achieving an R2 value of 0.999. Applying this optimized solvent mixture in UAE, xanthone concentration increased by up to 12 % compared to VCO alone with α-mangostin reaching 83.167 mg/g MP, with a linear relationship observed between ultrasound intensity, extraction time, and xanthone yield. The kinetics of UAE were effectively modeled using Peleg’s model, the pseudo-second-order kinetic model type 2, and the Response Surface Method. This mixed solvent method offers a more efficient and sustainable alternative to single-solvent, representing a significant advancement in xanthone extraction technology. The plant oil-based binary solvent developed in this study introduces a novel option for researchers working on the extraction of green plant compounds. Furthermore, it holds promising applications across various chemical engineering industries.